Cinemagoing in District Six, Cape Town, 1920s to 1960s: History, politics, memory. (January 2017) - Maingard, Jacqueline
Drawing on recorded and transcribed life history interviews conducted during the 1980s and 2000s, this article discusses the cinemagoing experiences of District Six residents in Cape Town from the 1920s to the 1960s, before the South African apartheid government began, from 1966, to demolish District Six. Cinemagoing was the chief leisure-time activity in District Six in these years, and when recollections of cinemagoing in the interviews are analysed as discourses of memory, three key themes emerge – cinema and place; cinema, culture, and identity; and films, film shows, and stars – with residents' remembered experiences revealing the peculiarities of cinemagoing in this very particular locale. Cinema was so thoroughly intertwined with everyday life that residents might be regarded not so much as 'going to' the cinema as already being there. They were part of a global seam of filmgoers – 'cinema citizens' whilst in every other respect stripped of citizenship rights.